Phylotranscriptomics reveals the phylogeny of Asparagales and the evolution of allium flavor biosynthesis - Xiao-Xiao Wang; Chien-Hsun Huang; Diego F. Morales-Briones; Xiang-Yu Wang; Ying Hu; Na Zhang; Pu-Guang Zhao; Xiao-Mei Wei; Kun-Hua Wei; Xinya Hemu; Ning-Hua Tan; Qing-Feng Wang; et al. (Nature Communications)
Abstract Asparagales, the largest monocot order, is renowned for its ecological, economic, and medicinal significance. Here, we leverage transcriptome data from 455 Asparagales species to explore the phylogeny of Asparagales. Moreover, we investigate the evolutionary patterns of the genes involved in allium flavor formation. We not only establish a robust bifurcating phylogeny of Asparagales but also explore their reticulate relationships. Notably, we find that eight genes involved in the biosynthesis of allium flavor compounds underwent expansion in Allium species. Furthermore, we observe Allium-specific mutations in one amino acid within alliinase and three within lachrymatory factor synthase. Overall, our findings highlight the role of gene expansion, increased expression, and amino acid mutations in driving the evolution of Allium-specific compounds. These insights not only deepen our understanding of the phylogeny of Asparagales but also illuminate the genetic mechanisms underpinning specialized compounds.